Race May Not Effect Outcomes in Operatively Treated Tibia Fractures - Piposar, Jonathan (Springer-Verlag, 2011)
BACKGROUND: A recent review of the literature found worse outcomes and longer length of stay for minorities undergoing TKAs and THAs when compared with whites. It is unclear if this association exists for the operative treatment of tibia fractures. QUESTIONS/PURPOSES: The purpose of this study is to determine if there is a difference in etiology or the rate of complications for operative treatment of tibia fractures as a function of racial heritage. Secondary objectives include definition of etiology, mechanism, and fracture location as a function of race in the urban setting, and an attempt to determine if differences in etiology or complications depend on race and fracture location for tibial plateau or shaft fractures. METHODS: A retrospective chart review was conducted at our Level 1 urban trauma center from January 1, 2005 to December 31, 2009 using ICD-9 code 823 to identify patients with tibia fractures. Charts were reviewed to confirm operative intervention, location of fracture, mechanism, demographic data, length of stay, and complications (infection, reoperation, compartment syndrome, deep venous thrombosis, pulmonary embolism, death). RESULTS: There was no difference in the rate of infection within 90 days with respect to race. There also was no difference in the rate of reoperation, deep venous thrombosis, pulmonary embolism, mortality, and length of stay between white patients and minority patients. Subgroup analysis showed no difference in the rate of infection for plateau or shaft fractures. Compartment syndrome was more frequent in white patients, specifically white patients with tibia shaft fractures. Minority patients were more likely to have a gunshot wound as a mechanism of injury. CONCLUSION: With the possible exception of an increased risk of compartment syndrome in white patients, there is no difference in outcomes with respect to race for operatively treated tibia fractures, regardless of fracture location. Gunshot wounds have become an increasingly prevalent mechanism of injury in minority patients. LEVEL OF EVIDENCE: Level IV, prognostic study. See the Guidelines for Authors for a description of levels of evidence.